FOXM1 could serve as a bridge mediating prognosis and immunity for clear cell renal cell carcinoma via single-cell and bulk RNA-sequencing - Jianhua Zhou; Zhuxian Xu; Yang Yu; Bingye Zhu; Qianwei Xing (Discover Oncology)
Abstract Background In the development of several cancers, the Forkhead Box M1 (FOXM1) is crucial. The relationship between the immune system and FOXM1 in renal cell carcinoma (ccRCC), which has been verified by bulk RNA sequencing and scRNA sequencing, is the primary subject of this research. Method Publicly available data related to FOXM1 and ccRCC were extracted from The Cancer Genome Atlas (TCGA) database. The impact of FOXM1 on the prognosis of ccRCC was examined using Cox regression analysis. Results were verified by immunohistochemistry and quantitative real-time PCR (qRT-PCR). Additionally, single-cell sequencing data were analyzed. Results When compared to para-carcinoma tissues, the expression of FOXM1 was considerably higher in ccRCC tissues. Patients with elevated FOXM1 expression had lower survival rates. FOXM1 may be a standalone prognostic factor for ccRCC, according to results of univariate and multivariate Cox regression studies. Reduced FOXM1 expression was linked to higher immunotherapy sensitivity, according to immunocorrelation analysis. This suggests FOXM1 may mediate immunotherapy resistance in ccRCC. Additionally, FOXM1 showed strong associations with tumor mutation load, microsatellite instability, and antitumor immunity. These results imply FOXM1 may regulate antitumor immunity in the ccRCC microenvironment. Consistent results from immunohistochemistry, PCR, and single-cell RNA sequencing confirmed upregulated FOXM1 expression in ccRCC. Conclusions According to the findings, FOXM1 might be used as a stand-alone prognostic biomarker for ccRCC. Moreover, FOXM1 has exhibited robust correlations with microsatellite instability, tumor mutation burden, immune response, and immunotherapy efficacy. FOXM1 may promote ccRCC pathogenesis partly by suppressing antitumor immunity and mediating immunotherapy resistance.